MODEL MANAJEMEN PEMBELAJARAN SEJARAH TERINTEGRASI PENDIDIKAN MULTIKULTURAL UNTUK MEMBANGUN WAWASAN KEBANGSAAN - Musadad, Akhmad Arif (History Department, Semarang State University and Historian Society of Indonesia, 2015)
The objective of the research is to describe: (1) prior condition of nationality insight among the students of Senior High Schools in Surakarta`, (2) the historical learning management conducted so far, (3) the form of need for the historical learning management model integrated in multicultural education, and (4) the form of historical learning management model integrated in multicultural education in Senior High Schools in Surakarta. This research is conducted using research and development designs. The subjects of research are students and history teachers of Senior High Schools in Surakarta. This study is conducted in explorative way using observation, interview, document analysis, instrument and FGD as techniques of collecting data. The data analysis is carried out using an interactive model of qualitative analysis. The result of research shows: (1) the nationality insight among the students is relatively low; (2) the teachers manage historical learning poorly, as identified from their low abilities of planning, organizing, implementing and evaluating the learning; (3) the teachers highly require the model of historical learning management integrated into multicultural education; and (4) the model of historical learning management integrated in multicultural education consists of learning planning, organization, implementation and evaluation steps. Tujuan penelitian ini adalah untuk mendeskripsikan: (1) kondisi awal tentang wawasan kebangsaan di kalangan siswa SMA Kota Surakarta, (2) bentuk manajemen pembelajaran sejarah yang selama ini dilaksanakan, (3) bentuk kebutuhan terhadap model manajemen pembelajaran sejarah terintegrasi pendidikan multikultural, dan (4) bentuk model manajemen pembelajaran sejarah terintegrasi pendidikan multikultural di SMA Kota Surakarta. Penelitian ini dilaksanakan dengan desain research and development. Subjek penelitiannya adalah siswa dan guru sejarah SMA di Kota Surakarta. Penelitian ini dilakukan secara eksploratif dengan teknik pengumpulan data menggunakan observasi, wawancara, analisis dokumen, angket dan FGD. Metode analisis data menggunakan analisis kualitatif model interaktif. Hasil penelitian menunjukkan: (1) wawasan kebangsaan di kalangan siswa relatif rendah; (2) guru kurang mampu mengelola pembelajaran sejarah, hal itu teridentifikasi dari rendahnya kemampuan merencanakan, mengorganisasikan, melaksanakan, dan mengevaluasi pembelajaran; (3) guru sangat membutuhkan model manajemen pembelajaran sejarah terintegrasi pendidikan multikultural; dan (4) model manajemen pembelajaran sejarah terintegrasi pendidikan multikultural terdiri atas langkah-langkah perencanaan pembelajaran, pengorganisasian pembelajaran, pelaksanaan pembelajaran, dan evaluasi pembelajaran.